Exploring pre-service student teachers’s experiences on reflective practice - Hanafi, Munirah; Hashim, Che Noraini (Open Access Reviewed Journal, 2014)

(untitled)
Reflective practice is viewed as the best component for developing effective teachers. Reflections act as a tool to bridge between teaching knowledge and teaching practice. This study draws on the perceptions of pre-service student teachers’ on the practice of writing reflections in the Bachelor of Teaching (Hons.) TESL program. The purpose of this study is to examine student teachers’ perceptions whether or not writing reflections would help them to develop understanding in teaching knowledge. It also aims at evaluating whether or not the goals of the Institute of Teacher Education Malaysia (ITEM) such as ‘developing knowledgeable, competent and expert teachers through reflective practice’ had been fulfilled. This study had been carried out over a period of six weeks. Three student teachers were interviewed using semi-structured interview schedule. Student teachers were also asked to write an overall reflection based on a course which they had attended in the program – the reflections focused on what they had learned during the course The reflections were analysed based on emerging themes. Findings from this study had indicated that writing reflections seemed to be helpful to student teachers’ understanding in teaching knowledge.